임상 실습 종합 평가로서 시행한 객관구조화진료시험 (OSCE) - 이화 의대의 경험 - 한재진(Jae Jin Han); 박혜숙(Hyesook Park); 어은경(Eunkyung Eo); 유경하(Kyungha Yoo); 이동현(Donghyeon Lee); 정화순(Wha Soon (Korean journal of medical education, 2004)
Purpose: To report the experience of OSCE performed as a summative assessment of the medical students in year 4 at Ewha Womans University. Methods: Ninety-eight students took the twenty stations including 3 pairs of linked stations. We conducted duplicated OSCEs and each station runs 4 minutes 30 seconds. We analyzed the validity of stations, the reliability of duplicated OSCEs and the difference of scores according to the OSCE tools and categories. Results: Mean OSCE score was 64.45±5.49 and Cronbach-α of total stations was 0.74. The scores between duplicated examinee groups and between duplicated evaluator groups were not different: the score of preceding examinee group was 63.3 and the later 65.7(p=0.13), and the score of the first evaluator group was 64.6 and the second was 63.6(p=0.16). However according to the individual analysis, 9 stations showed statistically discrepancies(p<0.05) between duplicated evaluator groups. Regarding OSCE tools and categories, physical examination and skill categories did not show statistically significant differences between duplicated evaluator groups. OSCE scores showed moderate correlation with the cummulative performance grade in general(r=0.53, p<0.01). Conclusions: OSCE could be regarded as a reasonable evaluating tool for the summative assessment after two years of clinical clerkship of the fourth year medical students. Analysis of the OSCE stations which was done individually and according to OSCE tools/categories helps to improve the OSCE more complete and the duplicated stations more coincident. KCI Citation Count: 7